(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saidy AR, Priatmadi BJ, Septiana M. 2022. Diversity in characteristics of tropical peatlands varying in land uses leads to differences in methane and carbon dioxide emissions. Biodiversitas 23: 6293-6301. The use of tropical peatlands for commercial agriculture causes a change in their original function as carbon storage to become sources of methane (CH4) and carbon dioxide (CO2) emissions. Therefore, this research aims to quantify the emission of CH4 and CO2, and peat characteristics in five tropical peatlands with different land uses, namely shrubs-, burned-, Albizia-, spring onion-, and lettuce-peatlands, to determine factors controlling carbon emissions. The results showed that CH4 emission ranged from 0.21 to 0.58 mg C m-2 h-1, with the lowest and the highest obtained in burned- and cultivated-peatlands (spring onion- and lettuce peatlands), respectively. The emission of CO2 ranged from the lowest in burned peatland (34.10-47.06 mg C m-2 h-1) to the highest in shrubs-peatland (136.79-180.87 mg C m-2 h-1). This showed that the diversity in CH4 emissions with different land uses is attributed to variations in the water table, water-filled pore space, ammonium, and nitrate contents. The rates of CO2 emission were controlled by carbohydrate-, fiber-, organic C-, and lignin-contents. This indicated that land and water managements need to be applied to reduce the emissions of CH4 and CO2 in tropical peatlands with different land uses.